Response of Shallots of Batu Ijo Variety on Doses of N And K Fertilizers - Widodo, Widodo; Marlin, Marlin; Sitio, Nancy B. (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2021)
Shallots (Allium cepa var. Aggregatum L) have many varieties that can be grown in the highlands and lowlands and one of them is the Batu Ijo variety. Nutrients N and K play an important role for plant needs. This research was conducted from March to June 2019 in Medan Baru, Bengkulu City. This study used a completely randomized design with two factors. The first factor was the dose of N fertilizer and the second factor was the application of K fertilizer. The application of N fertilizer had a significant effect on the number of shallots at week 2. The Urea dose given decreases the number of spring onions. For the best treatment at plant height is the treatment of Urea 300 kg/ha and KCl 50 kg/ha. Plant growth from week 2 to 5 increased significantly. The application of K fertilizer has an effect on the number of shallots at week 2 and the number of tubers. The higher the plant age, the more the number of leaves produced, but at higher doses, the number of leaves and the number of tubers decreased. The best treatment for the number of leaves produced was Urea 300 kg/ha and without giving KCl. For the best treatment of fresh plant weight, namely Urea 300 kg/ha and KCl 150 kg/ha, the best treatment fresh tuber weight was Urea 300 kg/ha and KCl 150 kg/ha, for tuber diameter the best treatment was 200 kg/ha of urea and KCl 100 kg/ha and for the number of tubers of Urea 0 kg/ha and KCl 150 kg/ha.Keywords: shallots, N fertilizer, K fertilizer